Bionic grinding machine design for thin shell removal from cassia seeds - Yuan, Xinyu; Huang, Caojun; Gao, Xuewen; Tong, Shangyu; Li, Yifei; Yi, Shujuan (International Journal of Agricultural and Biological Engineering, 2025)
In order to address the challenge of low efficiency in removing the thin shells from cassia seeds, a bionic grinding machine was developed for the removal of thin shells from cassia seeds during pharmaceutical processing, inspired by the hand-rubbing motion observed in traditional manual methods. The machine features a grinding-suction disk assembly integrated with a negative pressure feeding system. Flow rate calculations were performed to support the design, although specific parameters require further elaboration. A single-chip microcontroller (SCM)-based control system enables real-time parameter adjustment via a human–machine interface, ensuring precise control throughout the grinding process. After prototype fabrication, single-factor experiments established parameter ranges for orthogonal testing. The optimal parameter combination was identified as a grinding layer gap of 2.4 mm, a rotational frequency of 170 r/min, and a grinding duration of 12 s, resulting in a grinding degree of 9.07% and a shell removal cleanliness of 4.51%. Image-based surface feature analysis confirmed the machine’s effectiveness in removing thin shells, supporting its applicability in pharmaceutical seed processing. This study introduces a novel and efficient mechanized approach for cassia seed thin shell removal, which enhances the efficiency of thin shell removal and provides meaningful support for the advancement of pharmaceutical seed processing technologies. Key words: cassia seed; grinding; automatic control system; test; light reflectivityDOI: 10.25165/j.ijabe.20251806.9532Citation: Yuan X Y, Huang C J, Gao X W, Tong S Y, Li Y F, Yi S J. Bionic grinding machine design for thin shell removal from cassia seeds. Int J Agric & Biol Eng, 2025; 18(6): 269–280.